A synchrotron X-radiography study of the fragmentation and refinement of primary intermetallic particles in an Al-35 Cu alloy induced by ultrasonic melt processing. (December 2017) - Wang, Feng; Eskin, Dmitry; Mi, Jiawei; Wang, Chuangnan; Koe, Billy; King, Andrew; Reinhard, Christina; Connolley, Thomas
Abstract : Abstract Using synchrotron X-ray high speed radiography, the fragmentation and refinement of pre-existing primary Al2 Cu intermetallic dendrites induced by ultrasonic melt processing in a hypereutectic Al-35% Cu alloy were studied in-situ and in real time. The alloy was melted, contained and processed in a quartz tube crucible with a middle section of approximately 300 μm-thick channel where the observations were made. Direct observation of intermetallic fragmentation and detachment unambiguously confirms that the acoustic cavitation and streaming flow play a crucial role in fragmentation of the intermetallic dendrites. Furthermore, the remelting effect due to transport of hot liquid via acoustic streaming flow and the stress against the intermetallic dendrites caused by acoustic streaming flow are found to be the dominant fragmentation mechanism in the present experiments. It is also suggested that cavitation bubbles or bubble clouds contribute to fragmentation not only by mechanically fracturing the dendrites but also by facilitating the effect of acoustic streaming flow on dendrites. At last, clear observation of equiaxed intermetallic dendrites growing from small fragments after ultrasonic melt processing provides the first conclusive evidence of the refinement mechanism, i.e. the acoustic cavitation and acoustic streaming flow progressively break the intermetallic dendrites into small fragments. Most of these small fragments are able to survive and then act as nuclei for the subsequent solidification of intermetallic phases, consequently leading to intermetallic refinement in the solidified microstructure. Graphical abstract: Image 1